A Controlled Trial of Gluten-Free Diet in Patients With Irritable Bowel Syndrome-Diarrhea: Effects on Bowel Frequency and Intestinal Function - Vazquez–Roque, Maria I.; Camilleri, Michael; Smyrk, Thomas; Murray, Joseph A.; Marietta, Eric; O'Neill, Jessica; Carlson, Paula; Lamsam, Jesse; Janzow, Denise; Eckert, Deborah; Burton, Duane; Zinsmeister, Alan R. (Gastroenterology (New York, N.Y. 1943), 2013)
Patients with diarrhea-predominant irritable bowel syndrome (IBS-D) could benefit from a gluten-free diet (GFD). We performed a randomized controlled 4-week trial of a gluten-containing diet (GCD) or GFD in 45 patients with IBS-D; genotype analysis was performed for HLA-DQ2 and HLA-DQ8. Twenty-two patients were placed on the GCD (11 HLA-DQ2/8 negative and 11 HLA-DQ2/8 positive) and 23 patients were placed on the GFD (12 HLA-DQ2/8 negative and 11 HLA-DQ2/8 positive). We measured bowel function daily, small-bowel (SB) and colonic transit, mucosal permeability (by lactulose and mannitol excretion), and cytokine production by peripheral blood mononuclear cells after exposure to gluten and rice. We collected rectosigmoid biopsy specimens from 28 patients, analyzed levels of messenger RNAs encoding tight junction proteins, and performed H&E staining and immunohistochemical analyses. Analysis of covariance models was used to compare data from the GCD and GFD groups. Subjects on the GCD had more bowel movements per day (P = .04); the GCD had a greater effect on bowel movements per day of HLA-DQ2/8–positive than HLA-DQ2/8–negative patients (P = .019). The GCD was associated with higher SB permeability (based on 0−2 h levels of mannitol and the lactulose:mannitol ratio); SB permeability was greater in HLA-DQ2/8–positive than HLA-DQ2/8–negative patients (P = .018). No significant differences in colonic permeability were observed. Patients on the GCD had a small decrease in expression of zonula occludens 1 in SB mucosa and significant decreases in expression of zonula occludens 1, claudin-1, and occludin in rectosigmoid mucosa; the effects of the GCD on expression were significantly greater in HLA-DQ2/8–positive patients. The GCD vs the GFD had no significant effects on transit or histology. Peripheral blood mononuclear cells produced higher levels of interleukin-10, granulocyte colony-stimulating factor, and transforming growth factor-α in response to gluten than rice (unrelated to HLA genotype). Gluten alters bowel barrier functions in patients with IBS-D, particularly in HLA-DQ2/8–positive patients. These findings reveal a reversible mechanism for the disorder. Clinical trials.govNCT01094041.